Hubungan Dukungan Keluarga Terhadap Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Fe Di PMB Lismayani Lubis Kab. Simalungun Tahun 2023 - Lismayani Lubis; Basaria Manurung (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The most common anemia in pregnancy is iron anemia, this is caused by a lack of iron intake in food due to reabsorption disorders, digestive disorders and bleeding. This research aims to determine the relationship between family support and compliance with pregnant women in consuming Fe tablets at PMB Lismayani Lubis, Simalungun Regency in 2023. This type of research is research using an analytical survey with a cross-sectional method approach. The population is all 46 pregnant women visiting PMB Lismayani Lubis, Simalungun Regency. The number of samples used was 46 people obtained using the total sampling technique. The data analysis technique uses chi square. The results obtained in this study were that from 46 respondents, there was a relationship between family support and compliance with pregnant women in consuming Fe tablets, showing that the p value = 0.012 < 0.05. It is recommended that health workers increase education regarding the administration of Fe tablets to pregnant women.